Formulation of Microwave-Assisted Natural-Synthetic Polymer Composite Film and Its Physicochemical Characterization. (26th December 2021) - Ullah, Aman; Khan, Nauman Rahim; Khan, Muaz Habib; Mehmood, Saima; Khan, Jahangir; Iftikhar, Tayyaba; Gul, Inam Ullah; Basit, Hafiz Muhammad; Qayum, Mughal; Shah, Shefaat Ullah
Abstract : This study is aimed at microwave-assisted synthesis of sodium carboxymethylcellulose and Eudragit L100 composite film and its physicochemical characterization. The film was developed with varying quantities of each polymer and treated with microwave at a fixed frequency of 2450 MHz with a power of 350 Watts for 60 and 120 s. All formulations were characterized for thickness/weight uniformity, moisture adsorption, erosion and water uptake, tensile strength, and vibrational, thermal, and surface morphological analysis in comparison with untreated film samples. Results indicated that microwave treatment for 60 s significantly improved the tensile strength, reduced the water adsorption, delayed erosion, and reduced the water uptake in comparison with the untreated and 120 s treated film formulations. The vibrational analysis revealed rigidification of hydrophilic domains at OH/NH moiety and fluidization of hydrophobic domains at asymmetric and symmetric CH moieties, which is envisaged to be due to the formation of new linkages between the two polymers. These were later confirmed by thermal analysis where a significant rise in transition temperature, as well as enthalpy of the system, was recorded. The microwave treatment for 60 s is thus advocated to be the best treatment condition for developing sodium carboxymethylcellulose and Eudragit L100 composite polymeric films.